6-Cyano Analogues of Bedaquiline as Less Lipophilic and Potentially Safer Diarylquinolines for Tuberculosis - Tong, Amy S. T. (ACS Med Chem Lett, 2017)
[Image: see text] Bedaquiline (1) is a new drug for tuberculosis and the first of the diarylquinoline class. It demonstrates excellent efficacy against TB but induces phospholipidosis at high doses, has a long terminal elimination half-life (due to its high lipophilicity), and exhibits potent hERG channel inhibition, resulting in clinical QTc interval prolongation. A number of structural ring A analogues of bedaquiline have been prepared and evaluated for their anti-M.tb activity (MIC(90)), with a view to their possible application as less lipophilic second generation compounds. It was previously observed that a range of 6-substituted analogues of 1 demonstrated a positive correlation between potency (MIC(90)) toward M.tb and drug lipophilicity. Contrary to this trend, we discovered, by virtue of a clogP/M.tb score, that a 6-cyano (CN) substituent provides a substantial reduction in lipophilicity with only modest effects on MIC values, suggesting this substituent as a useful tool in the search for effective and safer analogues of 1.